Institusionalisasi akad muamalah - Ali Amin Isfandiar (FEBI IAIN Langsa, 2020)
Islamic contract mechanism, as it's called al-'aqd al-muamalah) was doneas personal contract. The emerging of islamic bank makes it transfrormed being aninstitution contract, that changes a simple contract being a rigid one, because aposition of the islamic bank. This process is called by